The Best m-Term Trigonometric Approximations of the Classes L_β ,p^Ψ in Uniform Metric - Fedorenko, A. S.; Fedorenko, O.S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain an exact order estimate for the best approximation of the classes L_β ,p^Ψ of functions of one variable in the space L_∞.